Epigenetic control of type III interferon expression by 8-oxoguanine and its reader 8-oxoguanine DNA glycosylase1 - Xue, Yaoyao; Pan, Lang; Vlahopoulos, Spiros; Wang, Ke; Zheng, Xu; Radak, Zsolt; Bacsi, Attila; Tanner, Lloyd; Brasier, Allan R.; Ba, Xueqing; Boldogh, Istvan (Frontiers in Immunology, 2023)
Interferons (IFNs) are secreted cytokines with the ability to activate expression of IFN stimulated genes that increase resistance of cells to virus infections. Activated transcription factors in conjunction with chromatin remodelers induce epigenetic changes that reprogram IFN responses. Unexpectedly, 8-oxoguanine DNA glycosylase1 (Ogg1) knockout mice show enhanced stimuli-driven IFN expression that confers increased resistance to viral and bacterial infections and allergen challenges. Here, we tested the hypothesis that the DNA repair protein OGG1 recognizes 8-oxoguanine (8-oxoGua) in promoters modulating IFN expression. We found that functional inhibition, genetic ablation, and inactivation by post-translational modification of OGG1 significantly augment IFN-λ expression in epithelial cells infected by human respiratory syncytial virus (RSV). Mechanistically, OGG1 bound to 8-oxoGua in proximity to interferon response elements, which inhibits the IRF3/IRF7 and NF-κB/RelA DNA occupancy, while promoting the suppressor NF-κB1/p50-p50 homodimer binding to the IFN-λ2/3 promoter. In a mouse model of bronchiolitis induced by RSV infection, functional ablation of OGG1 by a small molecule inhibitor (TH5487) enhances IFN-λ production, decreases immunopathology, neutrophilia, and confers antiviral protection. These findings suggest that the ROS-generated epigenetic mark 8-oxoGua via its reader OGG1 serves as a homeostatic thresholding factor in IFN-λ expression. Pharmaceutical targeting of OGG1 activity may have clinical utility in modulating antiviral response.